Quorum sensing gene regulation in Staphylococcus epidermidis reduces the attraction of Aedes aegypti (L.) (Diptera: Culicidae) - Kim, Dongmin; Crippen, Tawni L.; Jordan, Heather R.; Tomberlin, Jeffery K. (Frontiers in Microbiology, 2023)
Introduction Identifying mechanisms regulating mosquito attraction to hosts is key to suppressing pathogen transmission. Historically, the ecology of the host microbial community and its influence on mosquito attraction, specifically, whether bacterial communication through quorum sensing (QS) modulates VOC production that affects mosquito behavior have not been extensively considered. Methods Behavioral choice assays were applied along with volatile collection, followed by GC-MS and RNA transcriptome analyses of bacteria with and without a quorum-sensing inhibitor, furanone C-30. Results Utilizing the quorum-sensing inhibitor on a skin-inhabiting bacterium, Staphylococcus epidermidis, we disrupted its interkingdom communication with adult Aedes aegypti and mitigated their attraction to a blood-meal by 55.1%. Discussion One potential mechanism suppressing mosquito attraction could be the reduction (31.6% in our study) of bacterial volatiles and their associated concentrations by shifting S. epidermidis metabolic (12 of 29 up regulated genes) and stress (5 of 36 down regulated genes) responses. Manipulating the quorum-sensing pathways could serve as a mechanism to reduce mosquito attraction to a host. Such manipulations could be developed into novel control methods for pathogen-transmitting mosquitoes and other arthropods.